2010
DOI: 10.1007/s10646-010-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the fate and effects of acetyl cedrene on Capitella teleta and sediment bacterial community

Abstract: "Investigation of the fate and effects of acetyl cedrene on Capitella teleta and sediment bacterial community" (2010). Valery Forbes Publications. 10. http://digitalcommons.unl.edu/biosciforbes/10 AbstractThe fate of the fragrance material, acetyl cedrene (AC), in sediment was examined in a 16 day laboratory experiment using the sediment microbial community subjected to the following treatments: AC (nominal concentration; 0 and 50 μg g −1 dw sediment) and macrofaunal worms (with/without Capitella teleta (forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(75 reference statements)
0
1
2
Order By: Relevance
“…Unlike HHCB, Dai et al found that after exposure for 14 days the level of sediment-associated acetyl cedrene (another fragrance material) was reduced by 88–99 and 13–31% in the sediment with and without C. teleta , respectively. However, another study reported that the level of acetyl cedrene in the sediment decreased by 72% in both treatments with and without C. teleta after 16 days . One explanation for these findings is that the microbial activity was very low initially in the study presented here due to the freezing of the sediment, which would potentially decrease the rate of microbial degradation compared to that of a fully active microbial community in previous studies.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Unlike HHCB, Dai et al found that after exposure for 14 days the level of sediment-associated acetyl cedrene (another fragrance material) was reduced by 88–99 and 13–31% in the sediment with and without C. teleta , respectively. However, another study reported that the level of acetyl cedrene in the sediment decreased by 72% in both treatments with and without C. teleta after 16 days . One explanation for these findings is that the microbial activity was very low initially in the study presented here due to the freezing of the sediment, which would potentially decrease the rate of microbial degradation compared to that of a fully active microbial community in previous studies.…”
Section: Discussioncontrasting
confidence: 52%
“…However, another study reported that the level of acetyl cedrene in the sediment decreased by 72% in both treatments with and without C. teleta after 16 days. 68 One explanation for these findings is that the microbial activity was very low initially in the study presented here due to the freezing of the sediment, which would potentially decrease the rate of microbial degradation compared to that of a fully active microbial community in previous studies. In addition, it seems that macrofaunal biotransformation is both species-and chemical-specific (e.g., ref 63).…”
Section: ■ Discussionmentioning
confidence: 66%
“…Unlike HHCB, Dai et al (2012) found that sediment-associated acetyl cedrene (another fragrance material) was reduced by 88-99% and 13-31% in the sediment with and without C. teleta, respectively, after 14 days of exposure. However, another study reported that acetyl cedrene in the sediment decreased 72% in both treatments with and without C. teleta after 16 days (Ellegaard-Petersen et al, 2010). One explanation for these findings is that the microbial activity was very low initially in the present study due to the freezing of the sediment, which would potentially decrease microbial degradation compared to a full-active microbial community in previous studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Consequently, the use (e.g., for laboratory rearing and experiments) and preparation of natural field‐collected sediment are often developed and evolved locally within research groups. For instance, the ecotoxicology group at Roskilde University has been using natural field‐collected sediment when studying sediment‐associated contaminants over the past several decades (see Ellegaard‐Petersen et al, 2010; Linke‐Gamenick et al, 1999; Nielsen et al, 2017; Palmqvist et al, 2003; Sandgaard, Syberg, et al, 2023; Selck et al, 1998, 2003a; Thit et al, 2015).…”
Section: Introductionmentioning
confidence: 99%